Pendekar Siber: empowering youth to combat cyber threats - Abdul Molok, Nurul Nuha (Sejahtera Centre of Sustainability and Humanity, 2023)
The book chapter features the experience of developing and executing the Pendekar Siber program at the International Islamic University Malaysia through research, teaching and learning. As an outcome of research, Pendekar Siber has four batches of students who have conducted self-empowerment program among youth in the area of cyber safety and security. It was done through IIUM's university required courses namely CCUB/SCSH 2163 Usrah in Action 1 and CCUB/SCSH 3164 Usrah in Action 2. Through these courses, IIUM students from various faculties were trained about cybersecurity, cyber safety, cyber ethics, cyber law, community engagement and Islamization topics. After that, these students conducted training and awareness programs in cyber safety and security to educate youth from B40 communities in urban poor areas.